RISE: Clinical clerkships for final year pharmacy students are possible during the COVID-19 pandemic!! / Dr Nur Wahida Zulkifli - Zulkifli, Nur Wahida (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Undergraduate pharmacy students, the final year students, are required to complete a hospital attachment to improve their understanding and appreciation of patient profiles from case scenarios and engagement with the patient. Once they graduate, they will be able to implement what they learned at university to apply in the workplace. However, due to the sheer COVID-19 pandemic, the student was unable to attach to the hospital.